TRANSFORMASI KONFLIK PASCA PERUSAKAN RUMAH IBADAT (STUDI KASUS GEREJA BAPTIS INDONESIA (GBI) SAMAN BANTUL TAHUN 2015) - Ajiyastuti, Retno (Program Studi Sosiologi Agama Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2018)
The issue of the construction of houses of worship in Indonesia often occurs because of rejection. This rejection often occurs because of the rejection of a group of majority religious in a region. Such rejection tends to lead to the emergence of conflicts that have also created various acts of violence experienced in both the escalation phase of the conflict and the de-escalation of the conflict. Conflicts that originate from outgroup, sometimes capable of causing divisions within the group. But over time, the phase de escalation of conflict can lead to an initiative to create sustainable peace. In this article, the author will present a description of the form of violence that occurred in the conflict of destruction of the Baptist Church of Indonesia (GBI) Saman by a group of Islamic organizations and explain how a conflict transformation in managing a post-conflict situation in the Dusun Saman Bantul. The transformation applied through some communicative actions based on the initiative of the member from in group Dusun Saman so as to create a positive peace in post-conflict situation. Keywords: conflict transformation, violence, GBI Saman, conflict Isu pendirian rumah ibadat di Indonesia kerap kali terjadi karena mengalami penolakan. Penolakan ini sering terjadi karena adanya penolakan dari sekelompok umat beragama mayoritas di suatu wilayah. Penolakan tersebut cenderung mengarah pada timbulnya konflik yang menciptakan pula berbagai tindak kekerasan yang dialami dalam fase eskalasi konflik maupun de eskalasi konflik. Dalam artikel ini, penulis akan memaparkan sebuah gambaran mengenai bentuk kekerasan yang terjadi di dalam konflik perusakan Gereja Baptis Indonesia (GBI) Saman oleh sekelompok ormas Islam serta menjelaskan bagaimana sebuah transformasi konflik dalam mengelola sebuah situasi pasca konflik di lingkungan Dusun Saman Bantul.